Weighing the risks of valproate in women who could become pregnant. (18th April 2018) - Angus-Leppan, Heather; Liu, Rebecca S N
Abstract : Despite international consensus on the harmful effects of valproate during pregnancy, women should not be denied the human right to make their own decisions after fully informed discussion, say Heather Angus-Leppan and Rebecca Liu